Single Nucleotide Polymorphism within the LDLR gene and responsiveness of cynomolgus macaque (Macaca fascicularis) to atherogenic diet - ACHMAD TAHER; DEDY DURYADI SOLIHIN; SULISTIYANI SULISTIYANI; DONDIN SAJUTHI; DEWI APRI ASTUTI (Society for Indonesian Biodiversity, 2016)
Taher A, Solihin DD, Sulistiyani, Sajuthi D, Astuti DA. 2016. Single Nucleotide Polymorphism within the LDLR gene and responsiveness of cynomolgus macaque (Macaca fascicularis) to atherogenic diet. Biodiversitas 17: 430-434. Genetic variation within low density lipoprotein receptor (LDLR) gene has been associated with normal variation of plasma lipid profiles and risks of coronary heart diseases (CHD) in human. Although cynomolgus macaque (Macaca fascicularis) is one of non-human primates commonly used as models in atherosclerosis research, little is known about the extent of polymorphism within the LDLR gene and its consequences on responsiveness to atherogenic diet. In this study, two regions of LDLR gene, namely exon 6 and intron 5, were sequenced in a sample of 22 male cynomolgus macaques which had differences in responsiveness to atherogenic diet. The objective of the study was to identify single nucleotide polymorphism (SNP) within the LDLR gene and to evaluate the kinds of haplotypes in relation to the responsiveness of the cynomolgus macaque to atherogenic diet. Sequence analysis revealed that there were two SNPs at exon 6, i.e. IVS5-6C > G and 825C > G, which were distributed in 3 haplotypes, and five SNPs at intron 5, i.e. g.IVS5+99T > C, g.IVS5+173G > T, g.IVS5+327A > G, g.IVS5âˆ’96C > T, and g.IVS5âˆ’6C > G, which were distributed in 6 haplotypes. It was found that haplotype II (GC) at 6 base pairs prior to the exon 6 and haplotype III (CGGTG) within the intron 5 were associated with hyporesponsiveness to atherogenic diet. The results showed that potential SNP existed within the exon 6 and intron 5 can be used as genetic markers for selecting hypo- from hyperresponders. Keywords: Hyporesponsiveness, LDLR gene, Macaca fascicularis, SNP